“Golden heads” in Marina Tsvetaeva’s dramatic works and her unfulfilled translation of Paul Claudel’s “Tête d’or” - Olga Shalygina (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
The message about unfulfilled translation of Paul Claudel’s drama “Tête d’or” by Marina Tsvetaeva appeared at the beginning of January 1921 in the socalled debate on “alterations” in the journal “Bulletin of the theatre”, published by the Theatre Department of Narkompros. In February 1921 Tsvetaeva wrote a refutation to the editorial board. A decisive rejection of translation could be affected not only by considerations of personal safety associated with merging the Theatre Department of Narkompros and the Political administration of the Revolutionary Military Council, but also by deeply internal creative processes. In a series of dramatic works written in 1918–19 (later called “Romance”), Tsvetaeva appeals to the innovative experience of Claudel in reforming the European drama. The article highlights the motif complex of “golden head”, genetically related to the image of Maximilian Voloshin and his mediation in the comprehension of Paul Claudel’s works by Russian culture. The key texts to highlight the complex motifs of the “golden head” in Tsvetaeva’s dramatic works are monologue of Gold-headed during the assumption of power, dialogues of Gold-headed and Princess on top of the world from Claudel’s drama “Tête d’or”, and the story of the New Year fire in Koktebel from Tsvetaeva's essay “The Living about Living”. Consideration of neo-mythological connections allows to expand the subject of Tsvetaeva’s unfulfilled translation of Paul Claudel’s “Tête d’or” for a performance in the Theater I of the RSFSR under the leadership of V.E. Meyerhold to consider ways of transformation of Claudel’s drama in Russian literature.